Manajemen Asuhan Keperawatan Pada Anak Dengan Disfungsi Kardiovaskular (Congestive Heart Failure) Pada Anak : Literature Review - Setyawati, Ari; Marwiati, Marwiati (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2017)
Background: Heart failure in children is an important cause of morbidity and mortality in childhood (Office et al., 2013). The most likely cause of a child's congestive heart failure depends on his or her age. Neonates and young infants from 2 months of age are the most likely age range for congestive heart failure associated with structural heart disease (Satou, 2015). The purpose of this literature review is used to analyze the importance of critical care with cardiovascular issues